Globalised minds, roots in the city. Urban upper-middle classes in Europe. - Andreotti, Alberta; Le Galès, Patrick; Moreno-Fuentes, Francisco Javier (Wiley-Blackwell, 2015)
The book utilises empirical evidence from four European cities to explore the role of urban upper middle classes in the transformations experienced by contemporary European societies. It presents new empirical evidence collected through an original comparative research about professionals and managers in four European cities in three countries, features an innovative combination of approaches, methods, and techniques in its analyses of European post-national societies and reveals how segments of Europe's urban population are adopting "exit" or "partial exit" strategies in respect to the nation state. Utilises approaches from classic urban sociology, globalization and mobility studies, and spatial class analysis. It includes in depth interviews, social networking techniques, and classic questions of political representation and values.
Keywords: Stadtsoziologie; Stadtforschung; Kultur; Urbanität; Großstadt; Einstellung; Mobilität; Stadtleben; Alltagskultur; Stadtgesellschaft; Mittelschicht; Manager; Städtevergleich; Ländervergleich; Mobilitätsforschung; Lebensstil; Konvergenz; Soziale Gruppe; Empirische Untersuchung; Kosmopolitismus; Auslandstätigkeit; Netzwerk